High-strength nano-particle reinforced high-temperature-resistant austenitic stainless steel and method for preparing the same

By mixing Ti powder and B4C powder in a ball mill at room temperature to form a nickel column of gradient-distributed mixed powder, and then melting, casting and water-cooling quenching in an induction melting furnace, high-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steel is prepared. This solves the problem of grain coarsening and brittle precipitates caused by dynamic recrystallization and grain boundary migration during high-temperature service of austenitic stainless steel, and improves high-temperature strength and plasticity.

CN120006174BActive Publication Date: 2025-11-18JILIN UNIVERSITY

Patent Information

Application Number
CN202510281107.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-11-18
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

During high-temperature service, existing austenitic stainless steels experience grain coarsening and strength reduction due to dynamic recrystallization and grain boundary migration. Brittle precipitates accumulate at grain boundaries, increasing the risk of intergranular fracture. These are problems that existing technologies cannot effectively solve.

Method used

High-strength nanoparticle-reinforced high-temperature austenitic stainless steel is obtained by layering Ti powder and B4C powder into a nickel thin tube using laser welding technology at room temperature, according to a certain method, in a ball mill, and by using a certain method to form a nickel column with gradient distribution of mixed powder. After melting, casting, homogenization and water quenching in an induction melting furnace, high-strength nanoparticle-reinforced high-temperature austenitic stainless steel is obtained.

Benefits of technology

It achieves technical effects such as high strength, plasticity, toughness and stability at high temperatures, improves the effectiveness of existing technologies, solves the problems of existing technologies, and demonstrates its effectiveness in solving technical problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120006174B_ABST
    Figure CN120006174B_ABST
Patent Text Reader

Abstract

The application provides a high-strength nano-particle reinforced high-temperature-resistant austenitic stainless steel and a preparation method thereof. The preparation method of the high-strength nano-particle reinforced high-temperature-resistant austenitic stainless steel comprises the following steps: firstly, Ti powder and B4C powder are mixed to obtain mixed powder; then the mixed powder and nickel powder are mixed in four proportions and sequentially placed into a nickel thin tube layer by layer from top to bottom according to a certain mass ratio; laser welding technology is used for welding to obtain a nickel column body with gradient distribution of the mixed powder; nano-particles are introduced into the stainless steel liquid by adding the nickel column body in the melting process of the austenitic stainless steel; and finally, the high-strength nano-particle reinforced high-temperature-resistant austenitic stainless steel is obtained after vacuum casting, high-temperature homogenization and solid solution quenching. The high-strength nano-particle reinforced high-temperature-resistant austenitic stainless steel obtained by the application has a yield strength of greater than or equal to 165 MPa and a tensile strength of greater than or equal to 347 MPa when used at a working temperature of 600 DEG C or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-temperature resistant materials technology, and in particular to high-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steel and its preparation method. Background Technology

[0002] Austenitic stainless steel possesses excellent structural stability, high strength, creep resistance, and superior resistance to steam oxidation and corrosion, making it a key candidate material for components in ultra-supercritical thermal power generation and advanced nuclear energy systems. However, when applied to core components such as superheaters and reheaters in ultra-supercritical boilers, stainless steel materials require even better high-temperature strength. However, austenitic stainless steel faces several challenges during long-term high-temperature (>500℃) service: on the one hand, dynamic recrystallization and grain boundary migration lead to grain coarsening, causing a sharp decline in high-temperature strength over time; on the other hand, internal elemental segregation induces the enrichment of brittle precipitates such as σ-phase and Laves phase at grain boundaries, causing a toughness-plasticity mismatch and significantly increasing the risk of intergranular fracture. This severely restricts the stability and reliability of austenitic steel in high-temperature environments and hinders the improvement of its high-temperature mechanical properties. Existing research has focused on improving high-temperature strength by adding large amounts of precious metal alloying elements for solid solution strengthening or by stabilizing the microstructure through multiple heating-cooling cycles. However, high solid solution strengthening leads to increased work hardening rates and easily induces brittle intermetallic phases. Moreover, above 600℃, atomic diffusion intensifies, easily leading to compositional segregation and decreased plasticity. The heat treatment process involving multiple heating-cooling cycles is costly and difficult to industrialize. Traditional solid solution strengthening and heat treatment methods are no longer sufficient to meet the demands of rapidly developing industries. Therefore, how to reduce costs, simplify processes, and improve the high-temperature strength of austenitic stainless steel while simultaneously enhancing its plasticity, stability, toughness, and other properties, and achieving industrialized production, are urgent technical problems that need to be solved. Summary of the Invention

[0003] To solve the above-mentioned technical problems, the present invention provides a high-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steel, comprising the following steps:

[0004] (1) At room temperature, Ti powder and B4C powder are placed in a ball mill at a mass ratio of 2.4:1-3.6:1 and mixed thoroughly in the ball mill at a speed of 40-70 rpm for 8-12 hours to obtain mixed powder 1;

[0005] The Ti powder has a particle size of 50-140 micrometers, and the B4C powder has a particle size of 20-200 micrometers.

[0006] (2) The mixed powder 1 obtained in step (1) is mixed with nickel powder in a ball mill at a speed of 55-65 rpm for 9-11 hours at mass ratios of 3.7:1-4.5:1, 2.8:1-3.5:1, 1.7:1-2.4:1 and 0.7:1-1.3:1 to obtain mixed powder 2, mixed powder 3, mixed powder 4 and mixed powder 5; the nickel powder has a particle size of 80-250 micrometers;

[0007] (3) The mixed powder 2, mixed powder 3, mixed powder 4 and mixed powder 5 described in step (2) are placed into the nickel thin tube layer by layer in the order from top to bottom according to the mass ratio of 0.8-1.2:0.8-1.2:0.8-1.2:5.6-8.4. Then, laser welding technology is used to weld them at a power of 750-950W and a welding speed of 20-35mm / s to finally prepare a nickel column with gradient distribution mixed powder.

[0008] (4) Under argon protection, austenitic stainless steel is heated to 1500-1600℃ in an induction melting furnace by increasing the power by 4-7KW every 8-12 minutes and holding for 20-30 minutes to obtain stainless steel melt. Then, nickel pillars of gradient distribution mixed powder obtained in step (3) are added until melted. After casting, homogenization treatment at 1200-1300℃ for 6-8 hours, solution treatment at 1050-1250℃ for 1-2.5 hours, and water quenching treatment are performed to obtain high-strength nanoparticle reinforced high-temperature resistant austenitic stainless steel. The mass ratio of the nickel pillars of gradient distribution mixed powder to austenitic stainless steel is 0.02%:1-0.07%:1.

[0009] The austenitic stainless steel composition, by weight percentage, is as follows: C: 0.03-0.13 wt.%; Cr: 16.00-19.00 wt.%; Si: ≤0.30 wt.%; Mn: ≤1.50 wt.%; V: ≤0.15 wt.%; P: ≤0.040 wt.%; S: ≤0.020 wt.%; Ni: 6.50-10.50 wt.%; B: 0.001-0.015 wt.%; Cu: 1.50-3.50 wt.%; Nb: 0.15-0.60 wt.%; N: 0.04-0.12 wt.%; Al: 0.002-0.030 wt.%; balance Fe.

[0010] The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel contains 10-35% of a high-temperature ferrite phase δ with a size of 15-45 μm. The high-temperature ferrite phase δ is dispersed in short chains at the grain boundaries and within the grains of austenite. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel contains uniformly dispersed nanoparticles with a particle size of 50-200 nm. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel has a yield strength ≥165 MPa and a tensile strength ≥347 MPa at temperatures of 600℃ and above.

[0011] Further, in step (1), Ti powder and B4C powder are placed in a ball mill at a mass ratio of 2.8:1 to 3.4:1 at room temperature.

[0012] Furthermore, the Ti powder in step (1) has a particle size of 60-120 micrometers, and the B4C powder has a particle size of 40-160 micrometers.

[0013] Further, the mixed powder 1 mentioned in step (2) is mixed with nickel powder in a ball mill at a speed of 56-63 rpm for 9.5-10 hours at mass ratios of 4.0:1-4.2:1, 3.0:1-3.2:1, 2.0:1-2.2:1 and 0.9:1-1.2:1 respectively.

[0014] Furthermore, the nickel powder particle size mentioned in step (2) is 90-160 micrometers.

[0015] Further, the mixed powders 2, 3, 4 and 5 mentioned in step (3) are placed into the nickel thin tube layer by layer in a mass ratio of 0.9-1.1:0.9-1.1:0.9-1.1:6.3-7.7 from top to bottom, and then laser welding technology is used to weld them at a power of 850-900W and a welding speed of 28-32mm / s.

[0016] Further, in step (4), the austenitic stainless steel is heated to 1540-1580℃ in an induction melting furnace by increasing the power by 5-6kW every 9-10 minutes and holding for 25-28 minutes to obtain stainless steel melt.

[0017] Further, in step (4), after homogenization treatment at 1250-1280℃ for 6.5-7.5 hours, followed by solution treatment at 1100-1200℃ for 1.5-2.3 hours and water quenching treatment, high-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steel is obtained.

[0018] Further, in step (4), the mass ratio of nickel column to austenitic stainless steel in the gradient distribution mixed powder is 0.03%:1-0.06%:1.

[0019] Further, the composition of the austenitic stainless steel mentioned in step (4) is as follows: C: 0.04-0.10 wt.%; Cr: 17.00-18.50 wt.%; Si: ≤0.20 wt.%; Mn: ≤1.00 wt.%; V: ≤0.10 wt.%; P: ≤0.030 wt.%; S: ≤0.010 wt.%; Ni: 7.50-9.50 wt.%; B: 0.002-0.010 wt.%; Cu: 2.50-3.00 wt.%; Nb: 0.20-0.50 wt.%; N: 0.05-0.11 wt.%; Al: 0.003-0.020 wt.%; with the balance being Fe. Attached Figure Description

[0020] Figure 1 This is a metallographic diagram of the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 1 in Example 2 of the present invention;

[0021] Figure 2 The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 1 in Example 2 of this invention has a high-temperature stress-strain curve at 600℃.

[0022] Figure 3 The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 1 in Example 2 of this invention has a high-temperature stress-strain curve at 650℃.

[0023] Figure 4 This is a metallographic diagram of the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 2 in Example 3 of the present invention;

[0024] Figure 5 The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 2 in Example 3 of this invention has a high-temperature stress-strain curve at 600℃.

[0025] Figure 6 The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 2 in Example 3 of this invention has a high-temperature stress-strain curve at 650℃.

[0026] Figure 7 This is a metallographic diagram of the austenitic stainless steel 3 in Comparative Example 1 of the present invention;

[0027] Figure 8 This is the high-temperature stress-strain curve of austenitic stainless steel 3 at 600℃ in Comparative Example 1 of this invention.

[0028] Figure 9 This is the high-temperature stress-strain curve of austenitic stainless steel 3 at 650℃ in Comparative Example 1 of this invention. Detailed Implementation

[0029] Example 1

[0030] The preparation method of a nickel column of gradient-distributed mixed powder includes the following steps:

[0031] Step 1: At room temperature, Ti powder and B4C powder are placed in a ball mill at a mass ratio of 3:1 and mixed thoroughly for 10 hours at a speed of 65 rpm to obtain mixed powder 1.

[0032] The Ti powder has a particle size of 70-90 micrometers, and the B4C powder has a particle size of 60-140 micrometers.

[0033] Step 2: Mix the mixed powder 1 obtained in Step 1 with nickel powder in a ball mill at a speed of 60 rpm for 8 hours at mass ratios of 4:1, 3:1, 2:1 and 1:1 respectively to obtain mixed powder 2, mixed powder 3, mixed powder 4 and mixed powder 5; the nickel powder has a particle size of 90-160 micrometers;

[0034] Step 3: The mixed powders 2, 3, 4 and 5 described in Step 2 are placed into the nickel thin tube layer by layer in a mass ratio of 1:1:1:7 from top to bottom. Then, laser welding technology is used to weld them at a power of 900W and a welding speed of 30mm / s to finally prepare a nickel column with gradient distribution mixed powder.

[0035] Example 2

[0036] High-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steel 1, its preparation method includes the following steps:

[0037] Under argon protection, austenitic stainless steel was heated to 1580℃ in an induction melting furnace by increasing the power by 5kW every 9 minutes and holding for 25 minutes to obtain stainless steel melt. Then, nickel pillars of gradient-distributed mixed powder obtained in Example 1 were added until the nickel pillars melted into the stainless steel melt. After casting, homogenization treatment at 1260℃ for 7.5 hours, solution treatment at 1150℃ for 2 hours, and water quenching treatment were performed to obtain high-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steel 1. The mass ratio of the nickel pillars of gradient-distributed mixed powder to austenitic stainless steel was 0.04%:1.

[0038] The composition of the austenitic stainless steel, by weight percentage, is as follows: C: 0.040 wt.%; Cr: 17.10 wt.%; Si: 0.20 wt.%; Mn: 0.75 wt.%; V: 0.07 wt.%; P: 0.020 wt.%; S: 0.0010 wt.%; H: 0.00035 wt.%; N: 0.065 wt.%; Nb: 0.24 wt.%; Ni: 7.58 wt.%; O: 0.0020 wt.%; balance Fe.

[0039] In this embodiment, the metallographic structure of the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 1 is as follows: Figure 1 As shown, the microstructure contains approximately 26% high-temperature ferrite phase δ with a size of approximately 20-40 μm. The high-temperature ferrite phase δ is dispersed in short chains at the grain boundaries and within the austenite. High-strength nanoparticle-reinforced high-temperature austenitic stainless steel 1 contains uniformly dispersed nanoparticles (nanoparticle size of 50-200 nm). Figure 2 and Figure 3 The figures show the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 1 in this embodiment, at 600℃ and 650℃ respectively. Its yield strength and tensile strength at 600℃ are 187MPa and 370MPa, respectively, and its yield strength and tensile strength at 650℃ are 165MPa and 347MPa, respectively. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 1 maintains high strength at high temperatures, while also maintaining high plasticity, stability, toughness and other properties.

[0040] Example 3

[0041] High-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steel 2 is prepared by the following steps:

[0042] Under argon protection, austenitic stainless steel was heated to 1585℃ in an induction melting furnace by increasing the power by 7kW every 8 minutes and holding for 28 minutes to obtain stainless steel melt. Then, nickel pillars of gradient-distributed mixed powder obtained in Example 1 were added until the nickel pillars melted into the stainless steel melt. After casting, homogenization treatment was carried out at 1260℃ for 7.3 hours, followed by solution treatment at 1150℃ for 2.2 hours and water quenching treatment to obtain high-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steel 2. The mass ratio of the nickel pillars of gradient-distributed mixed powder to austenitic stainless steel was 0.06%:1.

[0043] The composition of the austenitic stainless steel, by weight percentage, is as follows: C: 0.040 wt.%; Cr: 17.10 wt.%; Si: 0.20 wt.%; Mn: 0.75 wt.%; V: 0.07 wt.%; P: 0.020 wt.%; S: 0.0010 wt.%; H: 0.00035 wt.%; N: 0.065 wt.%; Nb: 0.24 wt.%; Ni: 7.58 wt.%; O: 0.0020 wt.%; balance Fe.

[0044] In this embodiment, the metallographic structure of the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 2 is as follows: Figure 4As shown, the microstructure contains 15% fine, short, strip-shaped high-temperature ferrite phase δ with a size range of 18-30 μm, and the high-temperature ferrite phase δ is relatively uniformly distributed; in addition, nanoparticles (with a particle size of 50-200 nm) are uniformly dispersed within it. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 2 obtained in this embodiment exhibits high-temperature tensile stress-strain curves at 600℃ and 650℃ as shown in the figure. Figure 5 and Figure 6 As shown, its yield strength and tensile strength at 600℃ are 196MPa and 376MPa, respectively, and its yield strength and tensile strength at 650℃ are 177MPa and 355MPa, respectively. High-strength nanoparticle reinforced high-temperature resistant austenitic stainless steel 2 has high strength at high temperatures while still maintaining good plasticity, stability, toughness and other properties.

[0045] Comparative Example 1

[0046] Austenitic stainless steel 3 is prepared by the following steps:

[0047] Under argon protection, austenitic stainless steel is heated to 1575℃ in an induction melting furnace by increasing the power by 8kW every 6 minutes and holding for 20 minutes to obtain austenitic stainless steel melt. Then, after casting, high-temperature homogenization treatment at 1250℃ for 7 hours, solution treatment at 1150℃ for 2.1 hours, and water quenching treatment, austenitic stainless steel 3 is obtained.

[0048] The composition of the austenitic stainless steel, by mass percentage, is as follows: C: 0.040 wt.%; Cr: 17.10 wt.%; Si: 0.20 wt.%; Mn: 0.75 wt.%; V: 0.07 wt.%; P: 0.020 wt.%; S: 0.0010 wt.%; H: 0.00035 wt.%; N: 0.065 wt.%; Nb: 0.24 wt.%; Ni: 7.58 wt.%; O: 0.0020 wt.%; balance Fe.

[0049] In this comparative example, austenitic stainless steel 3 and the high-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steel in the examples belong to the same series of austenitic stainless steels and are therefore comparable. Their metallographic structures are as follows: Figure 7 As shown, the austenitic stainless steel 3 obtained in Comparative Example 1 contains 48% high-temperature ferrite phase δ with a size of 70-80 μm. The coarse high-temperature ferrite phase δ is distributed in a long-chain, interwoven network at the austenite grain boundaries and within the grains. This large-size, coarse network of high-temperature ferrite phase δ is unfavorable for the use of austenitic stainless steel at high temperatures. The high-temperature tensile stress-strain curves of the austenitic stainless steel 3 obtained in Comparative Example 1 at 600℃ and 650℃ are shown below. Figure 8 and Figure 9As shown, the high-temperature yield strength and tensile strength at 600℃ are 160MPa and 346MPa, respectively, and the high-temperature yield strength and tensile strength at 650℃ are 152MPa and 321MPa, respectively.

[0050] The differences between Embodiments 2 and 3 of the present invention and Comparative Example 1 are as follows:

[0051] In Example 2, the content of high-temperature ferrite phase δ in the microstructure of the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 1 was significantly reduced compared to Comparative Example 1, decreasing from 48% to 26%. The high-temperature ferrite phase δ was significantly refined, with its size range decreasing from 70-80 μm to 20-40 μm. Moreover, the high-temperature ferrite phase δ in Example 2 broke the long-chain interwoven network structure of Comparative Example 1, instead exhibiting a short-chain dispersed distribution in the matrix. The coarse and relatively high proportion of network-like high-temperature ferrite phase δ in Comparative Example 1 was detrimental to improving the high-temperature strength of austenitic stainless steel. In contrast, the high-temperature ferrite phase δ obtained in this invention has a lower content, smaller size, and more uniform and dispersed distribution. It also forms uniformly distributed nanoparticles. The fine and uniformly dispersed high-temperature ferrite phase δ, the fine and dispersed distribution of the internal structure, and the nanoparticles achieve synergistic regulation with the matrix. In Example 2, the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 1 exhibits yield strength and tensile strength at 600℃ that are 16.9% and 6.9% higher than those of Comparative Example 1, respectively; and yield strength and tensile strength at 650℃ that are 8.6% and 8.1% higher than those of Comparative Example 1, respectively. Therefore, under high-temperature conditions, the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 1 obtained in Example 2 has significantly better strength than the austenitic stainless steel 3 obtained in Comparative Example 1. At the same time, the present invention enables stainless steel 1 to maintain high plasticity and thermal stability.

[0052] In Example 3, the high-temperature ferrite phase δ in the microstructure of the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 2 accounted for only 15%, significantly less than that in Comparative Example 1 (48%) of the austenitic stainless steel 3. Compared to Comparative Example 1, the high-temperature ferrite phase δ in Example 3 did not exhibit a long-chain interwoven network structure, but rather appeared as short strips uniformly and diffusely distributed in the matrix. Moreover, compared to Comparative Example 1, the size of the high-temperature ferrite phase δ in the microstructure of Example 3 was significantly reduced, decreasing from 70-80 μm to 18-30 μm, with a more uniform distribution, and also forming uniformly distributed nanoparticles. The smaller the size and the more uniformly dispersed the high-temperature ferrite phase δ in austenitic stainless steel, the better its high-temperature resistance, i.e., the higher its high-temperature strength. In Example 3, the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 2 exhibits yield strength and tensile strength at 600℃ that are 22.5% and 8.7% higher than those of Comparative Example 1, respectively; and yield strength and tensile strength at 650℃ that are 16.4% and 10.6% higher than those of Comparative Example 1, respectively. Moreover, the yield strength and tensile strength of the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 2 in Example 3 at 650℃ are still significantly higher than those in Comparative Example 1 at 600℃. Therefore, even when using a higher operating temperature than the Comparative Example, the high-temperature mechanical properties of the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 2 obtained in Example 3 are still significantly better than those of the austenitic stainless steel 3 obtained in Comparative Example 1.

[0053] Comparative Example 2

[0054] In their article "Study on High-Temperature Tensile Behavior and Deformation Microstructure of 304 Austenitic Stainless Steel" published in Materials and Processes, Tan et al. investigated the mechanical properties and deformation microstructure characteristics of 304 austenitic stainless steel at high temperatures. The tensile strength of 304 stainless steel at 600℃ was 255 MPa. The composition of the stainless steel, by mass percentage, was: C: 0.049 wt.%, Ni: 8.247 wt.%, Mn: 1.42 wt.%, Cr: 18.01 wt.%, Si: 0.0032 wt.%, Cu: 0.02 wt.%, with the balance being Fe.

[0055] Compared with Comparative Example 2, the differences between Example 2 and Example 3 are:

[0056] The high-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steels in Examples 2 and 3 of this invention are the same type of austenitic stainless steel as the 304 austenitic stainless steel in Comparative Example 2, and are therefore comparable. The proportion of alloying elements in the high-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steels obtained in Examples 2 and 3 (26.07 wt.%) is lower than that in Comparative Example 2 (27.75 wt.%). In particular, the contents of precious metal elements such as Cr (17.1 wt.%), Ni (7.58 wt.%), and Mn (0.75 wt.%) in the examples are all lower than those in Comparative Example 2 (18.01 wt.%). The content of Ni (8.247 wt.%) and Mn (1.42 wt.%) significantly reduces costs. Furthermore, in Example 2, the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 1 exhibits a tensile strength at 600℃ that is 45.1% higher than that of Comparative Example 2. In Example 3, the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 2 exhibits a yield strength at 600℃ that is 47.5% higher than that of Comparative Example 2. This demonstrates that the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel obtained by this invention, while costing less than existing technologies, still possesses significantly superior high-temperature mechanical properties compared to the austenitic stainless steel in Comparative Example 2. In addition, the tensile strength (355 MPa) of the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel 2 in Example 3 at 650℃ is significantly higher than the tensile strength (255 MPa) of the austenitic stainless steel in Comparative Example 2 at 600℃. This further illustrates that the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel obtained by this invention still possesses superior high-temperature mechanical properties compared to Comparative Example 2 at temperatures equal to or higher.

[0057] The comparison of the high-temperature mechanical properties of the austenitic stainless steel in the comparative example and the high-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steel in the examples is shown in Table 1 below:

[0058] Table 1 Comparison of high-temperature mechanical properties of austenitic stainless steel in comparative examples and various embodiments

[0059]

[0060] Compared with the comparative example and existing technologies, the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel obtained by the present invention, while reducing the amount of added elements and simplifying the process, shows a significant improvement in strength at 600℃ and above compared to the comparative example. Furthermore, the mechanical properties of the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel obtained in the embodiments of the present invention at 650℃ are still significantly better than those of existing stainless steel operating at 600℃. Simultaneously, the high-strength nanoparticle-reinforced high-temperature austenitic stainless steel obtained in the embodiments of the present invention exhibits a reduced content of high-temperature ferrite phase δ compared to the comparative example, with smaller size and more uniform distribution, while also forming uniform nanoparticles. While maintaining high strength at high temperatures, it also maintains comprehensive properties such as high plasticity, stability, and toughness suitable for high-temperature applications, significantly extending its service life and reliability under extreme conditions, making it suitable for industrial production. This invention breaks through the bottleneck of reduced alloy strength at high temperatures in existing technologies, and also overcomes the technical bottleneck of simultaneously improving strength, plasticity, toughness, and thermal stability in existing technologies, thus simultaneously improving the strength, plasticity, toughness, and thermal stability of stainless steel. The embodiments of this invention use different components, proportions, and process parameters, but the performance obtained is different. This shows that the best effect of this invention is not determined by a single component, proportion, process, or process parameter, but is achieved through the interaction of alloy components, proportions, processes, and process parameters. Moreover, the best technical effect can only be achieved within the scope of protection of the claims of this invention.

Claims

1. High-strength nanoparticle-reinforced high-temperature resistant austenitic stainless steel, characterized in that, Its preparation method includes the following steps: (1) At room temperature, Ti powder and B4C powder are placed in a ball mill at a mass ratio of 2.4:1-3.6:1 and mixed thoroughly in the ball mill at a speed of 40-70 rpm for 8-12 hours to obtain mixed powder 1; The Ti powder has a particle size of 50-140 micrometers, and the B4C powder has a particle size of 20-200 micrometers. (2) The mixed powder 1 obtained in step (1) is mixed with nickel powder in a ball mill at a speed of 55-65 rpm for 9-11 hours according to the mass ratios of 3.7:1-4.5:1, 2.8:1-3.5:1, 1.7:1-2.4:1 and 0.7:1-1.3:1 to obtain mixed powder 2, mixed powder 3, mixed powder 4 and mixed powder 5; the nickel powder has a particle size of 80-250 micrometers; (3) The mixed powder 2, mixed powder 3, mixed powder 4 and mixed powder 5 described in step (2) are placed into the nickel thin tube layer by layer in the order from top to bottom according to the mass ratio of 0.8-1.2:0.8-1.2:0.8-1.2:5.6-8.

4. Then, laser welding technology is used to weld them at a power of 750-950W and a welding speed of 20-35mm / s to finally prepare a nickel column with gradient distribution mixed powder. (4) Under argon protection, austenitic stainless steel is heated to 1500-1600℃ in an induction melting furnace by increasing the power by 4-7kW every 8-12 minutes and holding for 20-30 minutes to obtain stainless steel melt. Then, nickel pillars of gradient distribution mixed powder obtained in step (3) are added until melted. After casting, homogenization treatment at 1200-1300℃ for 6-8 hours, solution treatment at 1050-1250℃ for 1-2.5 hours, and water quenching treatment are performed to obtain high-strength nanoparticle reinforced high-temperature resistant austenitic stainless steel. The mass ratio of the nickel pillars of gradient distribution mixed powder to austenitic stainless steel is 0.02%:1-0.07%:

1. The austenitic stainless steel composition, by weight percentage, is as follows: C: 0.03-0.13 wt.%; Cr: 16.00-19.00 wt.%; Si: ≤0.30 wt.%; Mn: ≤1.50 wt.%; V: ≤0.15 wt.%; P: ≤0.040 wt.%; S: ≤0.020 wt.%; Ni: 6.50-10.50 wt.%; B: 0.001-0.015 wt.%; Cu: 1.50-3.50 wt.%; Nb: 0.15-0.60 wt.%; N: 0.04-0.12 wt.%; Al: 0.002-0.030 wt.%; balance Fe. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel contains 10-35% high-temperature ferrite phase δ with a size of 15-45μm, which is dispersed in short chains at the grain boundaries and within the grains of austenite. The nanoparticle-reinforced high-temperature austenitic stainless steel contains uniformly dispersed nanoparticles with a particle size of 50-200nm. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel has a yield strength ≥165MPa and a tensile strength ≥347MPa at temperatures of 600℃ and above.

2. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel according to claim 1, characterized in that, In step (1), Ti powder and B4C powder are placed in a ball mill at a mass ratio of 2.8:1 to 3.4:1 at room temperature.

3. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel according to claim 1, characterized in that, The Ti powder mentioned in step (1) has a particle size of 60-120 micrometers, and the B4C powder has a particle size of 40-160 micrometers.

4. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel according to claim 1, characterized in that, The mixed powder 1 mentioned in step (2) is mixed with nickel powder in a ball mill at a speed of 56-63 rpm for 9.5-10 hours at mass ratios of 4.0:1-4.2:1, 3.0:1-3.2:1, 2.0:1-2.2:1 and 0.9:1-1.2:1 to obtain mixed powder 2, mixed powder 3, mixed powder 4 and mixed powder 5.

5. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel according to claim 1, characterized in that, The nickel powder in step (2) has a particle size of 90-160 micrometers.

6. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel according to claim 1, characterized in that, In step (3), the mixed powders 2, 3, 4 and 5 are placed into the nickel thin tube layer by layer in a mass ratio of 0.9-1.1:0.9-1.1:0.9-1.1:6.3-7.7 from top to bottom, and then laser welding is performed at a power of 850-900W and a welding speed of 28-32mm / s.

7. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel according to claim 1, characterized in that, In step (4), the austenitic stainless steel is heated to 1540-1580℃ in an induction melting furnace by increasing the power by 5-6kW every 9-10 minutes and holding for 25-28 minutes to obtain stainless steel melt.

8. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel according to claim 1, characterized in that, Step (4) involves homogenization treatment at 1250-1280℃ for 6.5-7.5 hours, followed by solution treatment at 1100-1200℃ for 1.5-2.3 hours and water quenching to obtain high-strength nanoparticle-reinforced high-temperature austenitic stainless steel.

9. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel according to claim 1, characterized in that, The mass ratio of nickel column to austenitic stainless steel in the gradient distribution mixed powder described in step (4) is 0.03%:1-0.06%:

1.

10. The high-strength nanoparticle-reinforced high-temperature austenitic stainless steel according to claim 1, characterized in that, The composition of the austenitic stainless steel mentioned in step (4) is as follows: C: 0.04-0.10 wt.%; Cr: 17.00-18.50 wt.%; Si: ≤0.20 wt.%; Mn: ≤1.00 wt.%; V: ≤0.10 wt.%; P: ≤0.030 wt.%; S: ≤0.010 wt.%; Ni: 7.50-9.50 wt.%; B: 0.002-0.010 wt.%; Cu: 2.50-3.00 wt.%; Nb: 0.20-0.50 wt.%; N: 0.05-0.12 wt.%; Al: 0.003-0.020 wt.%; balance Fe.

Citation Information

Patent Citations

  • Method of in-situ micro biphase nanometer ceramic particle strengthened steel

    CN109023082A

  • High-strength austenitic stainless steel and preparation method thereof

    CN113231648A

Cited By

  • High-strength heat-resistant stainless steel pipe and method for manufacturing the same

    CN122687075A